2009
DOI: 10.1538/expanim.58.141
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differences among C57BL/6 Substrains

Abstract: Abstract:The C57BL/6 mouse is the most well-known inbred mouse strain, and has been widely used as a genetic background for congenic and mutant mice. A number of C57BL/6 substrains have been derived from the C57BL/6 founder line and are reported to differ in several phenotypes. There are several major sources of C57BL/6 substrains for the biomedical research community. The importance of their genetic and phenotypic differences among substrains, however, has not yet been well recognized by biomedical researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
286
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 312 publications
(296 citation statements)
references
References 31 publications
5
286
1
4
Order By: Relevance
“…Although the two studies used the same a4 KO and WT progenitors (Ross et al, 2000) and they were back-crossed to C57BL6 mice for at least 10 generations, the C57BL6 substrain used for back-crossing in the Cahir et al (2011) study was not reported. This is an important distinction, as critical behavioral differences between the various C57BL6 substrains (in particular with C57BL6/J, the substrain used in our studies) have been reported (Mulligan et al, 2008;Mekada et al, 2009;Matsuo et al, 2010). Furthermore, the Cahir et al (2011) study used a different route of administration of nicotine (i.p.…”
Section: A6* Nachrs Subtypes In Nicotine Cppmentioning
confidence: 78%
“…Although the two studies used the same a4 KO and WT progenitors (Ross et al, 2000) and they were back-crossed to C57BL6 mice for at least 10 generations, the C57BL6 substrain used for back-crossing in the Cahir et al (2011) study was not reported. This is an important distinction, as critical behavioral differences between the various C57BL6 substrains (in particular with C57BL6/J, the substrain used in our studies) have been reported (Mulligan et al, 2008;Mekada et al, 2009;Matsuo et al, 2010). Furthermore, the Cahir et al (2011) study used a different route of administration of nicotine (i.p.…”
Section: A6* Nachrs Subtypes In Nicotine Cppmentioning
confidence: 78%
“…Apart from several singlenucleotide polymorphisms, the two strains differ in the nicotinamide nucleotide transhydrogenase gene, which bears a missense mutation, detected in the strain C57J. Moreover, the strain phenotype, such as body weight, insulin resistance, blood glucose levels were strongly dependent on the applied diet (Toye et al, 2005;Mekada et al, 2009;Nicholson et al, 2010;Montgomery et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most commonly used strain backgrounds for aging studies are C57BL/6J and C57BL/ 6JNia (note that these are not identical) (Mekada et al, 2009;Simon et al, 2013). This is due in part to the widespread use of these strains in biomedical research and the fact that the NIA has provided aged C57BL/ 6JNia animals to the research community for many years though the NIA Aged Rodent Colony.…”
Section: Use Of Animal Modelsmentioning
confidence: 99%